2021
DOI: 10.1038/s41598-021-02735-9
|View full text |Cite
|
Sign up to set email alerts
|

Placozoan fiber cells: mediators of innate immunity and participants in wound healing

Abstract: Placozoa is a phylum of non-bilaterian marine animals. These small, flat organisms adhere to the substrate via their densely ciliated ventral epithelium, which mediates mucociliary locomotion and nutrient uptake. They have only six morphological cell types, including one, fiber cells, for which functional data is lacking. Fiber cells are non-epithelial cells with multiple processes. We used electron and light microscopic approaches to unravel the roles of fiber cells in Trichoplax adhaerens, a representative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 136 publications
(192 reference statements)
0
7
0
Order By: Relevance
“…For instance, in Spongilla lacustris , a freshwater sponge, vCLEM was used with FIB-SEM to demonstrate that individual neuroid cells interact with multiple choanocytes, supporting a role in neuron-effector communication, and with their conserved genetic makeup, as putative neuronal ancestors 46 . Using array tomography and SBF-SEM, fibre cells in the Placozoa Trichoplax adhaerens were shown to contact multiple adjacent cell types and display evidence of phagocytic activity, suggesting a macrophage-like role in innate immunity that appeared early in metazoan evolution 224 . In symbiotic microalgae (the algal symbiont Phaeocystis cordata , in its acantharean host), reconstructions of FIB-SEM image series showed significant alterations in morphometric measures, reflecting interaction between the symbiont and controlling host 225 .…”
Section: Applicationsmentioning
confidence: 99%
“…For instance, in Spongilla lacustris , a freshwater sponge, vCLEM was used with FIB-SEM to demonstrate that individual neuroid cells interact with multiple choanocytes, supporting a role in neuron-effector communication, and with their conserved genetic makeup, as putative neuronal ancestors 46 . Using array tomography and SBF-SEM, fibre cells in the Placozoa Trichoplax adhaerens were shown to contact multiple adjacent cell types and display evidence of phagocytic activity, suggesting a macrophage-like role in innate immunity that appeared early in metazoan evolution 224 . In symbiotic microalgae (the algal symbiont Phaeocystis cordata , in its acantharean host), reconstructions of FIB-SEM image series showed significant alterations in morphometric measures, reflecting interaction between the symbiont and controlling host 225 .…”
Section: Applicationsmentioning
confidence: 99%
“…Previously, immunolabeling experiments suggested that the TCa V 2 channel is weakly expressed in fiber cells, which are located between the dorsal and ventral epithelia ( 5 ). We therefore co-labeled dissociated Trichoplax cells with RNAscope probes for the fiber cell marker FoxC ( 60 ), revealing an absence of labeling for TCa V 1 ( Fig. 4 L ) but weak labeling for TCa V 2 in a subset of fiber cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this labeling was weak and infrequent, and altogether, it is difficult to state with certainty that TCa V 2 is significantly expressed in fiber cells. Recently, fiber cells were shown to mediate innate immunity and wound healing and to express gene markers homologous to macrophage cells ( 60 ). Lastly, immunofluorescence and in situ hybridization experiments indicate that TCa V 1 is expressed in both dorsal and ventral epithelial cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Comments added to proof: When this manuscript was under review, Mayorova et al (2021) provided additional experimental evidence and highlighted the importance of placozoan fiber cells in regeneration, innate immunity, and phagocytosis emphasizing the significance of macrophage-like cells in the evolution of basal animal lineages.…”
Section: Discussionmentioning
confidence: 99%